Workplace attachment and the eco-restructuring of people-workplace relationships in China's extractive forestry. (June 2022) - Zhu, Liyuan; Lo, Kevin
Highlights: The eco-restructuring of people-workplace relationships. Examines the socio-psychological impact of the eco-transition of the forestry sector. Laid-off workers experienced the abrupt loss of workplace identity and dependency. Remaining workers experienced growing workplace attachment. The retirees felt few psychological impacts from the eco-transition. Abstract: The eco-transition of extractive industries poses significant challenges for workers, and there is growing concern about the negative impact caused by the transformation on extractive workers. Yet, the socio-psychological impact of the eco-transition remains poorly understood. Drawing from the theory of place attachment and a case study of a forestry-dependent community in China, this study examines how the logging ban policy shapes people-workplace relationships in the forestry sector among different groups—laid-off workers, remaining workers, and retirees. The findings show that the eco-restructuring of people-workplace relationships is central to the eco-transition of extractive industries and the process is complex and heterogenous. Laid-off workers and their kin experience the abrupt loss of workplace identity and dependency, which negatively affects their well-being. In contrast, the growing workplace attachment of the remaining workers can be observed as work units are maintained as the basic transition unit instead of being demolished, serving as stable sources of income for the workers and maintain functional dependency in the context of a lack of job opportunities in other economic sectors. The retirees experience few psychological impacts from the eco-transition as they continue to enjoy a stable pension and hold firm their workplace attachment derived from long-term living and working in the forestry industry. Nevertheless, population loss and out-migration pose challenges to the place attachment of workers and retirees. The findings offer new insight of how the eco-transition of extractive industries affects workers and draws attention to the non-material aspects of just transitions.